Immediate parent-infant skin-to-skin study (IPISTOSS): study protocol of a randomised controlled trial on very preterm infants cared for in skin-to-skin contact immediately after birth and potential physiological, epigenetic, psychological and neurodevelopmental consequences - Agnes Linnér; Björn Westrup; Karoline Lode-Kolz; Stina Klemming; Siri Lillieskold; Hanne Markhus Pike; Barak Morgan; Nils Johannes Bergman; Siren Rettedal; Wibke Jonas (BMJ Open)
Introduction In Scandinavia, 6% of infants are born preterm, before 37 gestational weeks. Instead of continuing in the in-utero environment, maturation needs to occur in a neonatal unit with support of vital functions, separated from the mother’s warmth, nutrition and other benefits. Preterm infants face health and neurodevelopment challenges that may also affect the family and society at large. There is evidence of benefit from immediate and continued skin-to-skin contact (SSC) for term and moderately preterm infants and their parents but there is a knowledge gap on its effect on unstable very preterm infants when initiated immediately after birth.Methods and analysis In this ongoing randomised controlled trial from Stavanger, Norway and Stockholm, Sweden, we are studying 150 infants born at 28+0 to 32+6 gestational weeks, randomised to receive care immediately after birth in SSC with a parent or conventionally in an incubator. The primary outcome is cardiorespiratory stability according to the stability of the cardiorespiratory system in the preterm score. Secondary outcomes are autonomic stability, thermal control, infection control, SSC time, breastfeeding and growth, epigenetic profile, microbiome profile, infant behaviour, stress resilience, sleep integrity, cortical maturation, neurodevelopment, mother-infant attachment and attunement, and parent experience and mental health.Ethics and dissemination The study has ethical approval from the Swedish Ethical Review Authority (2017/1135-31/3, 2019–03361) and the Norwegian Regional Ethical Committee (2015/889). The study is conducted according to good clinical practice and the Helsinki declaration. The results of the study will increase the knowledge about the mechanisms behind the effects of SSC for very preterm infants by dissemination to the scientific community through articles and at conferences, and to the society through parenting classes and magazines.Study status Recruiting since April 2018. Expected trial termination June 2021.Trial registration number NCT03521310 (ClinicalTrials.gov).